Implementing Smart box interactive learning media in English learning to improve first grade students"™ vocabulary: Research and development - Savitri, Ayutdia; Widagdo, Arif (Journal of English Language Teaching Innovations and Materials (Jeltim), 2025)
English language instruction at the primary school level frequently encounters challenges, particularly in developing pupils"™ vocabulary. This study aims to design and evaluate the effectiveness of Smart Box, an interactive learning medium intended to improve vocabulary acquisition among first-grade pupils at a local elementary school. The research employed a Research and Development (RD) methodology using the 4D model: Define, Design, Develop, and Disseminate. Expert validation confirmed the medium"™s suitability, with a media validity score of 92.1% and a material validity score of 96.6%. Experimental testing revealed a significant improvement in pupils"™ vocabulary proficiency, as evidenced by a paired-samples t-test result (p .05). Additionally, the normalised gain (N-Gain) score demonstrated an average increase of 0.71, which is considered moderate to high. The use of Smart Box also contributed to improved learner motivation and engagement. These findings suggest that Smart Box is an effective tool for supporting vocabulary development in primary English education. Future research is recommended to explore the integration of digital features or expansion to other subjects to enhance learning outcomes further.How to cite this paper: Savitri, A., Widagdo, A. (2025). Implementing Smart box interactive learning media in English learning to improve first grade students"™ vocabulary: Research and development. Journal of English Language Teaching Innovations and Materials (Jeltim), 7(1), 73"“77. http://dx.doi.org/10.26418/jeltim.v7i1.92290